2004
DOI: 10.1039/b403728f
|View full text |Cite
|
Sign up to set email alerts
|

N,O-diacylhydroxylamines—structures in crystals and solutions

Abstract: The structures of four N,O-diacylhydroxylamines (RCOHNOCOR', R, R'= Me, Ph) were determined in the solid state by X-ray diffraction and studied by NMR and IR spectroscopies in solution. The interpretation of the results was supported by ab-initio calculations of various tautomers and conformers, rotational barriers and chemical shifts. The results indicate the absence of OH tautomers (R-C(OH)=N-O-C(O)-R', N-acyloxyimidic acid); the NH tautomers (R-C(O)-NH-O-C(O)-R', O-acylhydroxamic acid) are present in DMSO s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…15 N NMR spectroscopy of 15 N-labelled 1 showed that this compound is an O-(rather than N-)acylated hydroxamate (11). This result is in accord with structural studies of similar O-acyl hydroxamates (22) and will be assumed to be true for all of the present compounds, as shown in the structural diagrams above. They are thus likely to be weak N-H acids (23).…”
Section: Resultssupporting
confidence: 90%
“…15 N NMR spectroscopy of 15 N-labelled 1 showed that this compound is an O-(rather than N-)acylated hydroxamate (11). This result is in accord with structural studies of similar O-acyl hydroxamates (22) and will be assumed to be true for all of the present compounds, as shown in the structural diagrams above. They are thus likely to be weak N-H acids (23).…”
Section: Resultssupporting
confidence: 90%
“…was added dropwise and the reaction mixture stirred at room temperature for 16 h, diluted with ethyl acetate and washed with water and NaHCO 3 . The collected organic phases were dried with anhydrous MgSO 4 and evaporated under reduced pressure to afford the desired product as a white solid; yield: 759 mg (86%); mp 157–158 °C (reported: mp 154–157 °C);40 1 H NMR (300 MHz, DMSO): δ =12.67 (bs, 1 H), 8.16–8.09 (m, 2 H), 7.92–7.89 (m, 2 H), 7.79–7.71 (t, J =7.5 Hz, 1 H), 7.64–7.53 (m, 5 H); 13 C NMR (75 MHz, DMSO,): δ =164.87, 164.37, 134.35, 132.34, 130.95, 129.48, 129.13, 128.68, 127.40, 126.88; ESI‐MS: m/z =242 (M + +1).…”
Section: Methodsmentioning
confidence: 99%
“…Schraml et al [282] have Schiff bases are a group of nitrogen-containing compounds showing tautomeric equilibria. Schraml et al [282] have Schiff bases are a group of nitrogen-containing compounds showing tautomeric equilibria.…”
Section: Tautomerismmentioning
confidence: 99%